Penggunaan Ampas Tahu untuk Meningkatkan Gizi Pakan Domba Lokal - M Duldjaman (Media Peternakan, 2004)
This study was carried out to evaluate the performance of lambs that given different amounts of soya cake waste. The amounts were 0, 100, 200 and 300 g as treatment 1, 2, 3 and 4. Twenty four male indigenous lambs fed ad libitum native grass hay (12.45 ± 1.67 kg) were devided into four groups. Randomized complete design was applied to this study. The effect of treatments was evaluated by analyses of variance and Duncan test. The results showed that the increase of soya cake waste, increased the intake of dry matter, crude protein, TDN, daily gain and feed efficiency  (P < 0.01). The intakes were 628 to 897 g dry matter, 77 to 140 g crude protein, 415 to 635 g TDN, 15 to 95 g daily gain and 0.024 to 0.110 feed efficiency, respectively. Key words: soy cake waste, lamb, hay, daily gain, feed efficiency